2019
DOI: 10.1016/j.est.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and characterisation of ultrasonic joints for Li-ion batteries to evaluate the impact on electrical resistance and temperature raise

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…The Ni layer exists discontinuously by pushing and moving down to the lower part of the weld in the good weld, indicating that there is a metallurgical bond between the foil and the strip. The main purpose of nickel plating is to prevent corrosion and to enhance the weldability of highly conductive materials [18]. This is because nickel has a higher thermal and electrical resistance than copper [19].…”
Section: Cross-section Analysismentioning
confidence: 99%
“…The Ni layer exists discontinuously by pushing and moving down to the lower part of the weld in the good weld, indicating that there is a metallurgical bond between the foil and the strip. The main purpose of nickel plating is to prevent corrosion and to enhance the weldability of highly conductive materials [18]. This is because nickel has a higher thermal and electrical resistance than copper [19].…”
Section: Cross-section Analysismentioning
confidence: 99%
“…The percentage change in resistance values for varying thicknesses of Al and Cu busbars are shown in Figure 4b. It is worth noting that similar changes in resistance value were obtained from the 2.0 mm Al busbar (i.e., 26.30%) and the 1. electric current, the electrical resistance is expressed as R = ρl/A, where ρ represents the resistivity, l is the length and A is the cross-sectional area [30,35]. Furthermore, Das et al [30] reported detailed theoretical analysis and simulation methodology for electrical and thermal characterisation based on a single tab-to-busbar joint.…”
Section: Joint Electrical Resistance Behaviourmentioning
confidence: 99%
“…An attempt has been made by Brand et al [29] to measure the electrical resistance at the UMW joint and they observed that maximum tensile load corresponded to lower electrical resistance when ultrasonic welding was employed to join two brass (CuZn37) test samples. Additionally, Das et al [30] reported the electrical resistance change and temperature rise at battery tab joints between the Al/Cu[Ni] tab to single Cu busbar assembly. However, extensive electrical and thermal characterisation of ultrasonic welded joints considering different busbar materials with varying thicknesses are missing from the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The impact on the unknown noise is gradually updated but ignored, in which the recursive partial least square method is introduced to identify the battery parameters online to achieve the accurate real-time charged state prediction purpose. And then, the variable variance Kalman filtering method is proposed to update the noise variance in real time in order to reduce the noise interference that results in the inaccurate charged state estimation values [26,[46][47][48]. The optimal unbiased maximum posterior time-varying estimator can be built to correct the noise statistics online, but the time-varying problem of model parameters cannot be solved effectively due to the accumulated calculation effect.…”
Section: Introductionmentioning
confidence: 99%